Contribution of Noncommunicable Diseases to Medical Admissions of Elderly Adults in Africa: A Prospective, Cross‐Sectional Study in Nigeria, Sudan, and Tanzania. Issue 8 (15th July 2014) - Akinyemi, Rufus O.; Izzeldin, Isameldin M. H.; Dotchin, Catherine; Gray, William K.; Adeniji, Olaleye; Seidi, Osheik A.; Mwakisambwe, Josephine J.; Mhina, Carl J.; Mutesi, Florence; Msechu, Helen Z.; Mteta, Kien A.; Ahmed, Mayada A. M.; et al.
<x xml:space="preserve">Abstract</x> Objectives To describe the nature of geriatric medical admissions to teaching hospitals in three countries in Africa (Nigeria, Sudan, Tanzania) and compare them with data from the United Kingdom. Design Cross‐sectional cohort study. Setting Federal Medical Centre, Idi‐Aba, Abeokuta, Nigeria; Soba University Hospital, Khartoum, Sudan; Kilimanjaro Christian Medical Centre, Moshi, Tanzania; and North Tyneside General Hospital, North Shields, United Kingdom. Participants All people aged 60 and older urgently medically admitted from March 1 to August 31, 2012. Measurements Data were collected regarding age, sex, date of admission, length of stay, diagnoses, medication, date of discharge or death, and discharge destination. Results In Africa, noncommunicable diseases (NCDs) accounted for 81.0% (n = 708) of admissions (n = 874), and tuberculosis, malaria, and the human immunodeficiency virus and acquired immunodeficiency syndrome accounted for 4.6% (n = 40). Cerebrovascular accident (n = 224, 25.6%) was the most common reason for admission, followed by cardiac or circulatory dysfunction (n = 150, 17.2%). Rates of hypertension were remarkably similar in the United Kingdom (45.8%) and Africa (40.2%). Conclusions In the elderly population, the predicted increased burden of NCDs on health services in Africa appears to have occurred. Greater awareness and some reallocation of resources toward NCDs may be required if the burden of such diseases is to be reduced.